A Nationwide Prevalence of Common Mental Disorders and Suicidality in Nepal: Evidence from National Mental Health Survey, 2019-2020 - Dhimal, Meghnath; Dahal, Sushma; Adhikari, Kriti; Koirala, Pallavi; Bista, Bihungum; Luitel, Nagendra; Pant, Sagun; Marahatta , Kedar; Shakya, Suraj; Sharma, Pawan; Ghimire, Sailaja; Gyanwali, Pradip; et al. (Journal of Nepal Health Research Council, 2022)
Background: Mental disorders account for a large portion of burden of disease. In Nepal, the prevalence of mental disorders has been rising steadily, but national and province level prevalence is not available. This study aims to assess the prevalence of common mental disorders and suicidality in Nepal.Methods: We conducted nationwide descriptive cross-sectional community-based prevalence study of mental disorders and suicidality among adults (aged 18 years and above) and adolescents (aged 13 to 17 years) in Nepal. We included a total of 9200 adults and 5888 adolescents from seven provinces of Nepal by using a multistage Probability Proportionate to Size sampling technique. Mental disorders and suicidality were assessed using translated and adapted Nepalese version of Mini International Neuropsychiatric Interview (MINI) for disorders, English version 7.0.2 for Diagnostic and Statistical Manual of Mental disorders,5th Edition (DSM-5). Data were entered in CSPro v7.2. Weighted estimates for different mental disorders were calculated.Results: The overall weighted lifetime prevalence of any mental disorder among adults and adolescents was estimated at 10% and 5.2%, respectively. Suicidality was present among 7.2% of the adult and 4.1% of the adolescent participants. Among adult participants, the current prevalence of suicidal thoughts and lifetime suicidal attempts were found to be 6.5% and 1.1%, respectively. Conclusions: This survey indicated that mental health problems are major public health concerns in Nepal that should not be overlooked. Hence, a multisectoral approach is needed to address the burden of mental health problems among adults and adolescents in Nepal.Keywords: National Mental Health Survey, Mental Disorder, MINI, Suicidality, Nepal